Analysis Of Coronal Plane Knee Joint Alignment And Its Classification In The South Indian Population Using The Cpak System - S, Gautham.; Praveen, M. (Journal of Neonatal Surgery, 2025)
Background: Kinematic alignment (KA) in total knee replacement (TKR) aims to restore native joint anatomy, yet population-specific data remains limited for South Indians. The Coronal Plane Alignment of the Knee (CPAK) classification categorizes knee phenotypes, but its applicability to South Indian populations with distinct biomechanics requires investigation. Methods: This retrospective study analyzed 200 knees (150 patients) with advanced osteoarthritis (Kellgren-Lawrence grade 3/4) at a South Indian institution (2022-2024). Standardized full-limb radiographs were assessed by two surgeons using Surgimap software. CPAK classification was applied based on arithmetic Hip-Knee-Ankle angle (aHKA) and Joint Line Obliquity (JLO). Results were compared with Western cohorts. Results: The cohort (mean age 62.4±8.7 years, 65% female) demonstrated: Predominant varus alignment (58% vs 43% Western; p<0.01) with mean aHKA -2.3°±3.5°. Steeper JLO (mean 172.7°±4.2° vs 175°-179° Western). Type II (varus/apex-distal) as most common phenotype (32% vs 21% Western; p=0.003). Higher prevalence of apex-distal JLO (64% vs Western norms). Excellent interobserver reliability (ICC 0.88-0.92) Conclusions: South Indian osteoarthritic knees exhibit distinct CPAK distributions with predominant varus alignment and steeper joint line obliquity compared to Western populations. These findings suggest: Mechanical alignment TKR may overcorrect native anatomy. Kinematic alignment requires population-specific modifications. Implant designs should accommodate narrower femurs and variable JLO. The study highlights the need for ethnicity-specific TKR strategies to optimize outcomes in South Indian patients. Further research should correlate CPAK phenotypes with long-term implant survivorship.